Modeling ameloblast-matrix interactions using 3D cell culture - Visakan, Gayathri; Bapat, Rucha Arun; Su, Jingtan; Moradian-Oldak, Janet (Frontiers in Physiology, 2022)
The distinct morphology adopted by ameloblasts during amelogenesis enables specializations that are highly stage specific and are involved intimately with the development of a hierarchical enamel microstructure. The molecular mechanisms that govern the development of an elongated and polarized secretory ameloblast morphology and the potential roles played by the enamel matrix proteins (EMPS) in this process are not fully understood. Thus far, the in vitro models that have been developed to mimic these early cell-matrix interactions have either been unable to demonstrate direct morphological change or have failed to adapt across ameloblast cell lines. Here, we use a recently established 3D cell culture model to examine the interactions between HAT-7 cells and the major enamel matrix proteins, amelogenin and ameloblastin. We demonstrate that HAT-7 cells selectively respond to functional EMPs in culture by forming clusters of tall cells. Aspect ratio measurements from three-dimensional reconstructions reveal that cell elongation is 5-times greater in the presence of EMPs when compared with controls. Using confocal laser scanning microscopy, we observe that these clusters are polarized with asymmetrical distributions of Par-3 and claudin-1 proteins. The behavior of HAT-7 cells in 3D culture with EMPs is comparable with that of ALC and LS-8 cells. The fact that the 3D model presented here is tunable with respect to gel substrate composition and ameloblast cell type highlights the overall usefulness of this model in studying ameloblast cell morphology in vitro.